Long-term behavioral responses to man-made disasters: Insights from the Agent Orange experiment in Vietnam - Ralitza Dimova; Ulrike Grote; Arnab K. Basu (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
Do man-made disasters induce permanent behavioral changes? Using unique panel data from Vietnam that experimentally elicit a particular behavioral preference, namely, risk tolerance, we analyze (i) whether individuals located in areas exposed to greater levels of contaminants from Agent Orange spraying during the Vietnam War are relatively more risk tolerant vis-àvis those who are located in less affected areas, (ii) whether risk tolerance declines and the willingness to invest increases with the decreasing intensity of the harm over time, and (iii) the socio-economic factors that impede out-migration from the heavily contaminated areas. We find that individuals located within Agent Orange affected areas have greater risk tolerance, but this risk tolerance exhibits a downward trend. Continued residency within the disaster-affected areas is primarily influenced by the ownership of physical assets.
Keywords: C93; D1; Q51; 330; Vietnam; Agent Orange; Risk Profiles; Propensity Score Matching